Laboratory Management of the Department of Office Management and Business Services in the Subject of Expertise Concentration at SMK Negeri 8 Makassar - Hikmah Hikmah; Muh. Darwis; Muh Nasrullah (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2026)
The management of the Office Management and Business Services laboratory at SMK Negeri 8 Makassar plays a crucial role in supporting practical learning activities. The laboratory serves as an essential facility for developing students’ practical skills and reinforcing theoretical understanding. Nevertheless, its implementation continues to face several challenges, including inadequate facilities and infrastructure, insufficient supporting equipment, and weak maintenance of laboratory resources. These limitations reduce the laboratory’s ability to function optimally in supporting effective learning processes. This study aims to examine how laboratory management is implemented within the subject of expertise concentration and to identify both supporting and inhibiting factors influencing the management process. A qualitative approach was employed to obtain an in-depth understanding of existing practices and challenges. Data were collected through observation, documentation, and interviews with relevant stakeholders involved in laboratory management. The findings indicate that, in the planning aspect, management activities include the preparation of laboratory usage schedules, planning for the procurement of tools and equipment, and the appointment of laboratory management personnel at the beginning of each semester. Although these planning activities are conducted systematically, budget limitations significantly hinder the realization of optimal equipment procurement. As a result, some laboratory needs cannot be fully met in accordance with learning requirements. In terms of organization, the laboratory has implemented a division of tasks and responsibilities. However, this has not been supported by a written and structured work plan, and the number of available management personnel remains limited. These conditions affect the effectiveness of task implementation and coordination among laboratory staff. Regarding control, preventive supervision has been carried out reasonably well through the establishment of laboratory regulations aimed at preventing damage and misuse of facilities. However, detective and corrective controls have not been implemented effectively due to the absence of an adequate monitoring system and the lack of regular evaluations. Therefore, improvements in planning, organizing, and controlling that are more systematic and sustainable are necessary to enhance the effectiveness of laboratory management at SMK Negeri 8 Makassar and to better support practical learning activities.